Pengaruh Dukungan Atasan dan Pelatihan Terhadap Kegunaan Sistem Akuntansi Keuangan Daerah: Studi Kasus pada Badan Keuangan Provinsi Gorontalo - Dinna Karolina; Niswatin; Hapsawati Taan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of support from superiors and training on the Regional Financial Accounting System in the Agency Gorontalo Province Finance. The type of method used in this research is a quantitative method with data collection techniques using a questionnaire survey. The number of respondents in this study was 66 respondents consisting of PNS and PTT in the fields of secretariat, revenue and accounting. budget and development of regional finances, assets and treasury. The tool used in this research uses multiple linear regression analysis. Based on the results of this research, it is known that support from superiors and training have a positive and significant effect on the regional financial accounting system in the Gorontalo Province financial agency.